Tata Kelola dan Tantangan Penyelenggaraan Inovasi Daerah di Indonesia - Alfi Rizky Rahmanda (Jurnal Transformasi Administrasi, 2022)
This paper aims to see and find out how governance and challenges in implementation of regional innovation in Indonesia. Article 34 of Law Number (UU) 11 of 2019 concerning the National System of Science and Technology, states that the Central Government and Regional Governments are required to develop Inventions and Innovations. In addition, Law Number 23 of 2014 concerning Regional Government has also mandated Regional Governments to be able to carry out regional innovations. Both regulations have mandated obligations and opportunities for the Central and Regional Governments to be able to innovate in order to encourage national development. This study uses a qualitative method with information in the form of notes and descriptive data contained in the text under study. In collecting data, using library research, namely by using primary sources in the form of reading materials such as books, journals, documents, and other literature. The results in this study are that there are still a number of challenges in implementing regional innovation in Indonesia, such as the lack of reporting and publication of regional innovation data, the ineffectiveness of data integration carried out, and challenges to the competence of apparatus resources in the management and implementation of regional innovations.